Teste rápido para detecção de HIV na atenção primária: a perspectiva de profissionais e gestantes durante o pré-natal em Porto Alegre - Ribas, Éthel de Almeida (Universidade do Vale do Rio dos Sinos, 2019)
According to data from the World Health Organization (2013), currently 35.3 million people are living with HIV worldwide. In Brazil, in 2012, 39,185 new AIDS cases were reported, representing an incidence of 20.2 cases per 100,000 inhabitants. Currently, according to Brazil/MS (2013), it is estimated that in the country approximately 718,000 people are living with HIV/AIDS. In the southern region of the country, we have the highest incidence of AIDS cases, with 30.9 cases per 100 thousand inhabitants, with Rio Grande do Sul in first place in this disgusting ranking, with 41.4 AIDS cases per 100 thousand inhabitants (BRASIL/MS, 2013). These values are understood to be very high, given the efforts of more than 20 years of national HIV/AIDS prevention and treatment policies. The current characteristic of the disease is its increase, especially in the younger population, and its large concentration in populations at greater risk and vulnerability. For example, in a study carried out in ten Brazilian municipalities between 2008 and 2009, with population groups over 18 years of age in a situation of greater vulnerability, they estimated that HIV prevalence rates were 5.9% among drug users, 10, 5% in men who have sex with men and 4.9% in sex workers. (BRAZIL/MS, 2013). This information portrays the present establishment of vulnerability in the characteristics of the spread of the disease.
Keywords: HIV; Teste rápido de HIV; Detecção de HIV; Gestantes; Pré-natal; Rapid HIV; HIV detection; Pregnant women; Prenatal; ACCNPQ::Ciências da Saúde::Saúde Coletiva